Phylogenetic relationships of the family Gryporhynchidae (Cestoda: Cyclophyllidea) inferred through SSU and LSU rDNA sequences. Issue 6 (20th September 2018) - Ortega-Olivares, M.P.; García-Varela, M.
Abstract: Tapeworms of the family Gryporhynchidae are endoparasites of fish-eating birds distributed worldwide. Currently the family contains 16 genera classified on the basis of the morphology of the rostellar apparatus, rostellar hooks and strobilar anatomy. However, the phylogenetic relationships among the genera are still unknown. In this study, sequences of the near complete 18S (SSU) and 28S (LSU) from rDNA of 13 species of gryporhynchids (adult specimens) representing eight genera ( Cyclustera, Dendrouterina, Glossocercus, Gryporhynchidae gen. sp., Neovalipora, Paradilepis, Parvitaenia, Valipora ) and one species of metacestode from fish ( Neovalipora ) were generated. Additionally, sequences of metacestodes of the genera Amirthalingamia, Neogryporhynchus, Paradilepis, Parvitaenia and Valipora from Africa recently added to the GenBank database were analysed. Phylogenetic relationships were inferred using maximum-likelihood (ML) and Bayesian inference of each (SSU and LSU) dataset. The phylogenetic analyses indicated that the family Gryporhynchidae is a well-supported monophyletic group within the Cyclophyllidea. The trees inferred with SSU and LSU datasets had similar topologies and suggested that the genera Glossocercus (two species sequenced) and Paradilepis (four spp.) are monophyletic. In contrast, Dendrouterina, Parvitaenia and Valipora are paraphyletic, suggesting that the species composition of these genera should be critically reviewed. Interestingly, species of the genera that use the same groups of definitive hosts such as herons (Ardeidae), cormorants (Phalacrocoracidae) and ibis (Threskiornithidae) are together in the phylogenetic tree, even though they differ markedly from each other in some morphological characters, especially shape and size of rostellar hooks.